FENOMENA PERILAKU AGRESI ANAK YANG MENGALAMI KEKERASAN DALAM KELUARGA (STUDI PADA SISWA KELAS 2 MI ISLAMIAH ROGOJAMPI BANYUWANGI) - Trianingsih, Rima (Universitas Nusantara PGRI Kediri, 2016)
Abstract: The results of monitoring and evaluation KPAI in 2012 at 9 provinces shows that 91% of children in Indonesia have experienced violence in the family. In September 2015, an Elementary School student in South Jakarta died after incidents of beatings done his friend. Based on the background above, problems in this research is